The Effects of Maternal Separation on Adult Methamphetamine Self-Administration, Extinction, Reinstatement, and MeCP2 Immunoreactivity in the Nucleus Accumbens - Lewis, Candace R.; Staudinger, Kelsey; Scheck, Lena; Olive, M Foster (Frontiers in Psychiatry, 2013)
The maternal separation (MS) paradigm is an animal model of early life stress. Animals subjected to MS during the first two weeks of life display altered behavioral and neuroendocrinological stress responses as adults. MS also produces altered responsiveness to and self-administration (SA) of various drugs of abuse including cocaine, ethanol, opioids, and amphetamine. Methamphetamine (METH) causes great harm to both the individual user and to society; yet, no studies have examined the effects of MS on METH SA. This study was performed to examine the effects of MS on the acquisition of METH SA, extinction, and reinstatement of METH-seeking behavior in adulthood. Given the known influence of early life stress and drug exposure on epigenetic processes, group differences in levels of the epigenetic marker methyl CpG binding protein 2 (MeCP2) in the nucleus accumbens (NAc) core were also investigated. Long-Evans pups and dams were separated on postnatal days (PND) 2-14 for either 180 (MS180) or 15 min (MS15). Male offspring were allowed to acquire METH SA (0.05 mg/kg/infusion) in 15 2-hr daily sessions starting at PND67, followed by extinction training and cue-induced reinstatement of METH-seeking behavior. Rats were then assessed for MeCP2 levels in the NAc core by immunohistochemistry. The MS180 group self-administered significantly more METH and acquired SA earlier than the MS15 group. No group differences in extinction or cue-induced reinstatement were observed. MS15 rats had significantly elevated MeCP2-immunoreactive cells in the NAc core as compared to MS180 rats. Together, these data suggest that MS has lasting influences on METH SA as well as epigenetic processes in the brain reward circuitry.